2020
DOI: 10.1021/acs.jpcc.0c05425
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Electrodeposition of Cu(111) onto an l-Cysteine Self-Assembled Monolayer on Au(111) and Epitaxial Lift-Off of Single-Crystal-like Cu Foils for Flexible Electronics

Abstract: Functional self-assembled monolayers (SAMs) of thiols on single-crystal metals provide two-dimensional (2D) soft templates for the highly ordered growth of crystalline materials. An epitaxial Cu(111) film is electrodeposited on a SAM of the amino acid l-cysteine on Au(111). Epitaxy is confirmed, with Cu(111) following the Au(111) in-plane and out-of-plane orientations with a small amount of twinned [511] orientation, which is shown by X-ray analysis. The mismatch between Cu(111) and the Au(111) substrate is −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The electrodeposited ordered Cu 2 O films could prove to be a low-cost and easily prepared precursor for the fabrication of ordered MOF films on a large scale. Cu-BTC films with a thickness about 740 nm can be produced on Cu 2 O/Au or on Au by a complete conversion without the detachment problem that usually occurs in the electrochemical oxidation of Cu metal to Cu-BTC . We also demonstrated a pathway for epitaxial lift-off of Cu-BTC foils that may provide a path to produce membranes for gas separation and selective sensing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrodeposited ordered Cu 2 O films could prove to be a low-cost and easily prepared precursor for the fabrication of ordered MOF films on a large scale. Cu-BTC films with a thickness about 740 nm can be produced on Cu 2 O/Au or on Au by a complete conversion without the detachment problem that usually occurs in the electrochemical oxidation of Cu metal to Cu-BTC . We also demonstrated a pathway for epitaxial lift-off of Cu-BTC foils that may provide a path to produce membranes for gas separation and selective sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Cu-BTC films with a thickness about 740 nm can be produced on Cu 2 O/Au or on Au by a complete conversion without the detachment problem that usually occurs in the electrochemical oxidation of Cu metal to Cu-BTC. 31 We also demonstrated a pathway for epitaxial lift-off of Cu-BTC foils that may provide a path to produce membranes for gas separation and selective sensing. ■ ASSOCIATED CONTENT…”
Section: ■ Conclusionmentioning
confidence: 97%
See 1 more Smart Citation
“…X-ray diffraction patterns, pole figures, and azimuthal scans were run on a high-resolution Philips X'Pert Materials Research diffractometer using the accessories and procedures outlined in our previous report. 43 SEM was done on a FEI Helios Nanolab microscope, and TEM was done on a FEI Tecnai F20 microscope.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A novel approach of stabilizing the freestanding metal layers inside the mechanically rigid support such as graphene is also taken. [ 45–48 ] Formation of 2D CuO patch in bilayered graphene (BLG) pore is experimentally observed and characterized by TEM analysis. Further, the same study also reveals that 2D CuO patch found in confinement of BLG exhibits a stable antiferromagnetic behavior.…”
Section: Introductionmentioning
confidence: 99%